THE EFFECT OF MICRO-SILICA ON THE MICROSCOPIC FEATURES OF THE UHPC COMPOSITE AND ITS INTER-FACIAL TRANSITION ZONE - Vladimír Hrbek; Zdeněk Prošek; Roman Chylík; Lukáš Vráblík (Acta Polytechnica CTU Proceedings)
The uplift of concrete overall macroscopic performance by way of alternative additives is commonly used technique. In case of ultra high performance concrete (UHPC), micro-silica is added to the mixture as a micro-filler to the structure of cement binder. As a result, the cementitious matrix macro-mechanical performance is elevated. This paper is aimed on the UHPC micro-scale enhancement by different micro-silica additive content in the mixture. More closely, the study investigate the impact of the micro-silica on the inter-facial transition zone (ITZ) between the binder matrix and basaltic aggregate.